2012
DOI: 10.3109/00498254.2012.670312
|View full text |Cite
|
Sign up to set email alerts
|

Effects of silver nanoparticles on rat hepatic cytochrome P450 enzyme activity

Abstract: Silver nanoparticles (AgNPs) are increasingly used in various products and consequentially the potential adverse effects associated with exposure to them are of concern. This study investigated the effects of AgNPs on the hepatic drug-metabolizing enzymes of the cytochrome P450 (CYP) families 1, 2 and 3, using both in vitro and in vivo biological assays. AgNPs were orally administered to Sprague-Dawley rats at various concentrations (0-1000 mg/kg body weight/day) for 2 weeks. No effect was found on the plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
36
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 26 publications
8
36
1
Order By: Relevance
“…These findings suggest that Ag-NPs at these concentrations and durations of exposure did not cause any significant dysfunction in rat liver cells. Consistent with our study, Kulthong reported that oral administration of 180-nm Ag-NPs at doses of 50, 100, 250, 500, and 1000 mg/kg/day for two weeks did not significantly alter the serum ALT or AST levels (27). Elevated ALP and plasma cholesterol, dilatation of the central vein and bile duct, and hyperplasia were found in rats after oral administration of 60-nm Ag-NPs at more than 300 mg/kg/day for 28 days (29).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These findings suggest that Ag-NPs at these concentrations and durations of exposure did not cause any significant dysfunction in rat liver cells. Consistent with our study, Kulthong reported that oral administration of 180-nm Ag-NPs at doses of 50, 100, 250, 500, and 1000 mg/kg/day for two weeks did not significantly alter the serum ALT or AST levels (27). Elevated ALP and plasma cholesterol, dilatation of the central vein and bile duct, and hyperplasia were found in rats after oral administration of 60-nm Ag-NPs at more than 300 mg/kg/day for 28 days (29).…”
Section: Discussionsupporting
confidence: 91%
“…According to the findings, this difference between the biochemistry parameters and expression of caspase-3 may be because activation of caspases happens only transiently in the early apoptotic stages (27), without yet affecting liver function.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…312 This pilot research only provides an indication of nanoparticles' effects on the metabolizing capability of the liver; it is possible that in vivo, the effects of silver nanoparticles on CYP enzymes are mitigated by additional protective mechanisms. The effects of nanoparticles on other functions, such as the secretion of bile, the synthesis of glucose and fatty acids, and blood iron content, are largely unknown.…”
mentioning
confidence: 99%